Motivation and Work Environment as Determinants of Employee Performance in Port-Warehouse Operationsn : A Qualitative Study at PT Yusen Logistics Indonesia - Akhmad Gifari Multazam; Natanael Suranta; Larsen Barasa; Brenhard Mangatur Tampubolon (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Port logistics efficiency is determined not only by the adequacy of infrastructure and the advancement of technology but also by the motivation of the workforce and the overall quality of the work environment. This study investigates how these two factors influence employee performance in the Warehouse Division of PT Yusen Logistics Indonesia. The research employed qualitative methods, gathering data through semi-structured interviews, field observations, and document analysis, with participation from warehouse workers, supervisors, and safety officers. Through thematic analysis, the study found that employee recognition and active supervisory engagement were key contributors to workforce motivation. The work environment, characterized by equipment reliability, safety culture, and yard capacity, directly impacted employee productivity. When both motivation and work environment were favorable, employees exhibited greater procedural compliance, increased throughput, and improved safety practices. In contrast, inadequate motivation and unfavorable work conditions resulted in inefficiencies, downtime, and higher risk-taking behaviors. This study’s findings provide insights into three key areas: maritime economics by highlighting labor’s critical role in port operations, social management by establishing the link between environmental quality and workforce productivity, and vocational education by shaping the training of cadets and practitioners. It underscores that sustainable port operations require human-centered strategies, in addition to infrastructure development. For better performance, companies should prioritize motivating their workforce and improving the work environment to foster a more efficient and safer operational setting.